Effect of magnesium, zinc, iron and boron application on yield and quality of cotton (Gossypium hirsutum) - ANKARANARAYANAN, K S; PRAHARAJ, C S; NALAYINI, P; BANDYOPADHYAY, K K; GOPALAKRISHNAN, N (The Indian Journal of Agricultural Sciences, 2010)
An experiment was carried out during 2003 and 2004 to study the effect of standard fertilizers for secondary and micronutrients, viz Mg, Zn, Fe and B on growth, yield and quality of upland cotton (Gossypium hirsutum L.) in South zone. Pooled data for 2 years indicated that specific fibre quality parameters, such as ginning per cent and uniformity ratio were significantly enhanced by micronutrient fertilization. Soil applied with FeSO4 @ 50 kg/ha registered highest ginning percentage of 39.2% and uniformity ratio of 50.2 relative to control values of 36.3% and 47.5, respectively. Fibre length was also significantly improved by soil application of borax @ 5 kg/ha. Besides quality, foliar sprays of MgSO4 @ 0.5% at 60, 75 and 90 days after planting and soil applied borax @ 5 kg/ha also raised the seed cotton yield by more than 18% (1 630 and 1 640 kg/ha, respectively) in comparison to control (1 380 kg/ha). Other quality traits, viz seed index, fibre strength, micronaire and fibre elongation and fibre quality index were not influenced by the application of micronutrient fertilizers.